Procedures in solving economic - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Problem and its relevance. Recently among national legal scholars and practitioners is growing interest in different ways of settling disputes between economic entities outside the state judiciary. Chapter II of the Commercial Code of Ukraine of 06.11.1991 fixed rule that economic agents have the right to decide controversial issues in the pretrial order. Thus, in accordance with Art. 5 GPK Ukraine side measures apply pre-trial settlement of commercial disputes by agreement among themselves, that conciliation is introduced as one of the alternative ways of resolving disputes. Alternative methods of dispute resolution allowing entrepreneurs to use additional; often more flexible legal mechanisms to resolve conflicts. Practices of conciliation in resolving commercial disputes shows their progressive enough as compared to the commercial courts they have certain advantages. First, the economic efficiency in solving conflicts, thus promoting economic exchange, stabilization of economic relations, improvement of business results. Second, the empowerment of the right to the protection of non-judicial entities and access to new ways of resolving disputes. Thirdly, the restriction of monopoly of state courts and to some extent reduce corruption pressure on businesses. Fourth, democratic review process disputes - election of judges by agreement of the parties, the impact on the formation of rules disputes and so on. Purpose of the article - to consider the current conciliation procedures applied in resolving commercial disputes. Analysis of research and publications. Some attention to the problems of reconciliation in his writings are paid to domestic and foreign authors as: A. Bobrov, Gojko O. Davydchenko D. Zozuliak Yu Zaharyascheva I. Eremenko G., Miller, D., K. Nosyryeva and others.